Comparison of Mean duration of Hospital Stay in COPD patients with Acute Exacerbations Treated with and without Prophylactic Azithromycin - Naqeeb Ullah, Muhammad Hanif, Dost Muhammad Khan, Najam ud Din, Habibullah, Ikram Ullah, Jamshed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Acute exacerbations of chronic obstructive pulmonary disease (AECOPDs) can lead to high frequencies and duration of hospitalization and mortality. Azithromycin is a class of antibiotic that possess both antimicrobial and anti-inflammatory properties. The aim of this study was to compare the mean duration of hospital stay in COPD patients presenting with acute exacerbations treated with and without prophylactic azithromycin. Objective: To compare the mean duration of hospital, stay in COPD patients presenting with acute exacerbations treated with and without prophylactic azithromycin Setting: Department of Pulmonology, Military Hospital, Rawalpindi. Study Design: Randomized controlled trial. Duration of study: Was 6 months from 1st Oct 2019 1st March 2020. Subject & Methods: All patients who fulfill the inclusion criteria and admitted in the department of Pulmonology, Military Hospital, Rawalpindi were included in the study. After taking informed written consent history was taken, clinical examination was done and patients were divided into two groups group A (prophylactic Azithromycin) & C (control without prophylactic Azithromycin). Outcome was checked by comparing both the groups for mean duration of hospital stay. Result: Out of 122 AECOPDs patients 77 (63.1%) were males & 45 (36.9%) were female with the mean age 43.1830+10.8170 years. The mean duration of hospital stay in group A was 4.2787+1.880 days while in group C it was 9.4262+2.224 days. Conclusion: Azithromycin prophylaxis therapy could effectively reduce the duration of hospital stay among patients with AECOPDs. However, it may bring increased adverse events and the emergence of resistance. A recommendation for its prophylactic use should weigh both the advantages and disadvantages. Keywords: chronic obstructive pulmonary disease, hospital stay, azithromycin.